Efficacy of subsequent treatments in patients with hormone-positive advanced breast cancer who had disease progression under CDK 4/6 inhibitor therapy (vol 23, 136, 2023) - Karacin, Cengiz; Oksuzoglu, Berna; Demirci, Ayse; Keskinkilic, Merve; Baytemur, Naziyet Kose; Yilmaz, Funda; Hacibekiroglu, Ilhan (Bmc, 2023)
[Abstract Not Available]